Determining water transport kinetics in limestone by dual-wavelength cavity ring-down spectroscopy - Browne, DE; Peverall, R; Ritchie, GAD; Viles, HA (American Chemical Society, 2022)
Water plays a major role in the deterioration of porous building materials such as those widely found in built heritage, influencing many physical, chemical, and biological decay processes. This article details a proof-of-principle study using near-infrared cavity ring-down spectroscopy (CRDS) to monitor the release of water and its artificially enriched isotopologues from small (ca. 25 × 25 × 5 mm) samples of limestone subject to drying by a fixed flow of nitrogen with varying levels of humidity and at room temperature and atmospheric pressure. Under low-humidity conditions, the drying kinetics are consistent with the well-established two-phase drying process exhibited by porous materials, namely, an initial constant drying rate period (phase I) followed by a falling drying rate period (phase II). The water diffusivity during phase II, DII, was measured (for Clipsham limestone) to be 3.0 × 10–9 ± 1 × 10–10 m2 s–1. The CRDS measurements allow spectroscopic determination of the total mass of water released by the sample, and the calculated values are in excellent agreement with gravimetric analysis. Importantly, the selectivity and sensitivity afforded by CRDS allows isotope analysis to be carried out, such that the flux of isotopically labeled water out of the sample can be determined under conditions of humidified flow where there may be a simultaneous ingress of water from the environment. Dual-wavelength CRDS distinguishes isotopic species, and it is demonstrated that the drying kinetics and physical properties of the samples are self-consistent when monitoring both HDO and H2O (for HDO, DII was 3.2 × 10–9 ± 4 × 10–10 m2 s–1). As the humidity levels in the flow increase, a departure from the distinct two-phase behavior is observed in the HDO drying curves. These new measurements of isotopically resolved mass fluxes will help refine models for drying mechanisms in porous media.